(untitled) (Mustansiria Dental Journal, 2018)
Ninety six patient aged between 12 – 50 years attending the college of dentistry , Al- mustansyria university and the investigators clinics , they were divided into two equal groups; 48 Patients suffering acute apical periodntitis ( painful ) were subjected to different antibiotics after drainage and their prognosis towards nonpainful chronic apical perioddontitis was observed and were as follows : 29.3% with Azithromycin, 20.8 % with ampicilline and 29.3% with ampicilline plus metronidazole with a total of 79.4 % . The second group, were 48 students aged 12- 20 years suffering from severe marginal gingivitis ( GI-3 ) and were subjected to different antibiotics after prophylaxis and some of them were kept on prophylaxis alone and their progress to mild marginal gingivitis ( G.I.1) was observed and were as follows :20.8 % with azithromycin , 16.7 % with ampicilline, 22.9 % with ampicilline plus metronidazole and 20.8 % with prophylaxis and oral hygiene practice alone with a total of 81.2 % showing no significant difference between prophylaxis alone and those with prophylaxis and antibiotics .